Exercises in helping skills : a training manual to accompany the skilled helper - Egan, Gerard (Monterey, Calif : Brooks/Cole Publishing Co., 1975)
Written by Gerard Egan, this manual parallels the main text, "The Skilled Helper, Sixth Edition," and allows students to practice communication skills and each of the steps of the model in private before using them in actual face-to-face helping interactions with others.
Keywords: Counseling; Helping behavior; Interpersonal relations -- Problems, exercises, etc; Counseling -- Problems, exercises, etc; Helping behavior -- Problems, exercises, etc